Dynamics of a 3-DOF parallel mechanism used for orientation applications - Itul, T.; Pisla, D. (2008 IEEE International Conference on Automation, Quality and Testing, Robotics, 2008)
In the paper dynamic studies regarding the possibility to use a 3-DOF parallel mechanism for the TV satellite antenna orientation or sun tracker are presented. The advantage to use a parallel mechanism consists of their good stiffness, very high accuracy and their capability to manipulate heavy loads. The algorithms for the kinematic models are solved. Dynamic equations are obtained by using the Newton-Euler formalism in two steps. The first step is to determine the relations between the spherical joint reaction forces and the kinematic parameters of the mobile platform. The second step is to determine the generalized active torques. Using a numerical and graphical simulation, the diagrams for the dynamics representation are computed.